2004
DOI: 10.1105/tpc.104.026930
|View full text |Cite
|
Sign up to set email alerts
|

Encounters between Dynamic Cortical Microtubules Promote Ordering of the Cortical Array through Angle-Dependent Modifications of Microtubule Behavior[W]

Abstract: Ordered cortical microtubule arrays are essential for normal plant morphogenesis, but how these arrays form is unclear. The dynamics of individual cortical microtubules are stochastic and cannot fully account for the observed order; however, using tobacco (Nicotiana tabacum) cells expressing either the MBD-DsRed (microtubule binding domain of the mammalian MAP4 fused to the Discosoma sp red fluorescent protein) or YFP-TUA6 (yellow fluorescent protein fused to the Arabidopsis a-tubulin 6 isoform) microtubule ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
297
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 237 publications
(317 citation statements)
references
References 55 publications
(70 reference statements)
20
297
0
Order By: Relevance
“…Under low CMT anchoring conditions, this model results in a limited collision-induced depolymerization probability, similar to the experimental observations in Arabidopsis petiole cells [Wightman and Turner, 2007]. The authors suggest that tighter CMT anchoring to the plasma membrane might explain the higher probability for collision-induced depolymerization observed in tobacco BY-2 cells [Dixit and Cyr, 2004b]. Based on these data, regulation of CMT anchoring to the plasma membrane is an important mechanism for controlling array organization.…”
Section: Cmt Interaction-oriented Modelssupporting
confidence: 82%
See 4 more Smart Citations
“…Under low CMT anchoring conditions, this model results in a limited collision-induced depolymerization probability, similar to the experimental observations in Arabidopsis petiole cells [Wightman and Turner, 2007]. The authors suggest that tighter CMT anchoring to the plasma membrane might explain the higher probability for collision-induced depolymerization observed in tobacco BY-2 cells [Dixit and Cyr, 2004b]. Based on these data, regulation of CMT anchoring to the plasma membrane is an important mechanism for controlling array organization.…”
Section: Cmt Interaction-oriented Modelssupporting
confidence: 82%
“…They developed a Monte Carlo simulation with a limited number of CMTs in the system where the nucleation process is not considered. Their simulations show that simple rules for CMT interactions extracted from real-cell experiments can result in a parallel CMT arrangement from a randomly arranged population [Dixit and Cyr, 2004b]. They found that both bundling and collision-induced depolymerization are necessary and sufficient for CMT organization, although this conclusion might be related to the restricted size of the simulations, as stated by the authors.…”
Section: Cmt Organization-oriented Modelsmentioning
confidence: 93%
See 3 more Smart Citations